THE PROBLEM OF ARCHITECTURE DESIGN IN A CONTEXT OF PARTIALLY KNOWN REQUIREMENTS OF COMPLEX WEB BASED APPLICATION "KSU FEEDBACK" - A. Spivakovsky; N. Klymenko; A. Litvinenko; Y. Storozhuk; D. Berezovsky; S. Tityenok (Kherson State University, 2013)
The problem of flexible architecture design for critical parts of "KSU Feedback" application which do not have full requirements or clearly defined scope. Investigated recommended practices for solving such type of tasks and shown how they are applied in "KSU Feedback" architecture.